Comparing the Effects of Lumbar-pelvic and Pelvic Belts on the Activity of Pelvic Muscles in Pregnant Women With Back and Pelvic Pain - Zhaleh Heydari; Gholamreza Aminian; Akbar Biglarian; Maryam Shokrpour; Mohammad Ali Mardani (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective The physical and hormonal changes occur in pregnant women, which may cause skeletal and muscular discomforts and back and pelvic pain. If the pelvic muscles mechanism is damaged, pelvic joints may have less stability, and the joint is more exposed to shearing force. As a result of this condition, the activity pattern of these muscles of the lumbar region may change, increased muscle activity compensates for the anterior forces, and bending moments may occur, especially when the abdomen volume is increased. In previous studies, the activity of pelvic muscles in the test of active straight leg raise (ASLR) was evaluated in pregnant women without using a pelvic belt. These belts are strapped at the level of the pelvic ring and do not fully support the lumbar region. The lumbar-pelvic belt can extend below the lower angle of the scapula, completely covering the lumbar region and supporting the waist and pelvis simultaneously. As a result, the whole body acts as a unit compared to a pelvic belt. The present study aims to compare the effect of the lumbar-pelvic belt with the pelvic belt in the activity of the pelvic muscles during the ASLR test of the lower limb in pregnant women with back and pelvic pain. Materials & Methods This was a clinical trial study on 48 pregnant women with pregnancy-related back and pelvic pain referred to the Kawsar Specialized and Subspecialty Clinic in Arak City, Iran. The sampling method was convenience sampling based on inclusion and exclusion. All participants completed the written consent form, and then they were randomly divided into three groups: lumbar-pelvic belt (14 women), pelvic belt (14 women), and control (20 women). First, a demographic questionnaire was completed by the participants. Then the pelvic muscles' muscle activity was evaluated using surface electromyography during the ASLR test at the beginning of the study and then three weeks later. Covariance analysis was used in SPSS version 26 software for data analysis, and the significance level was considered 0.05. Results After three weeks of using the devices, the activity of the right rectus femoris, left rectus femoris, right biceps femoris, and left biceps femoris muscles decreased in both groups who used the belts and increased in the control group during the ASLR test. The activity of the right biceps femoris and left biceps femoris muscles in the lumbar-pelvic belt group was significantly reduced compared to the pelvic belt group (P<0.001). Although the activity level of the right rectus femoris and left rectus femoris muscles in the lumbar-pelvic belt group decreased more than the pelvic belt group, this decrease was not statistically significant. Conclusion The activity of the rectus femoris and biceps femoris muscles during the ASLR test decreased in both groups using the pelvic belts and increased in the control group after three weeks. This finding shows the effect of both pelvic belts on improving pelvic muscle activity. However, the lumbar-pelvic belt had a greater impact on improving the activity of the biceps femoris muscles than the pelvic belt during the ASLR test.